2011
DOI: 10.1002/etc.599
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac in fish: Blood plasma levels similar to human therapeutic levels affect global hepatic gene expression

Abstract: Diclofenac is a nonsteroidal anti-inflammatory drug frequently found in the aquatic environment. Previous studies have reported histological changes in the liver, kidney, and gills of fish at concentrations similar to those measured in treated sewage effluents (approximately 1 µg/L). Analyses or predictions of blood plasma levels in fish allow a direct comparison with human therapeutic plasma levels and may therefore be used to indicate a risk for pharmacological effects in fish. To relate internal exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 45 publications
3
48
3
Order By: Relevance
“…This approach is based on receptor homology and other pathway similarities between fish and mammals (Valenti et al, 2012;Margiotta-Casaluci et al, 2014). A study by Cuklev et al (2011) specifically addressed the relationship between blood plasma levels of diclofenac in fish and effects on the molecular level; effects were discernible when plasma levels in the fish approached human therapeutic concentration (H T PC). Valenti et al (2012) observed significant decreases in binding at the therapeutic target and shelter-seeking behavior when fish plasma levels of sertraline exceeded H T PC, which was defined as either 142 ng mL À1 or 190 ng mL À1 .…”
Section: Relationships Between Responses and Plasma Concentrationsmentioning
confidence: 99%
“…This approach is based on receptor homology and other pathway similarities between fish and mammals (Valenti et al, 2012;Margiotta-Casaluci et al, 2014). A study by Cuklev et al (2011) specifically addressed the relationship between blood plasma levels of diclofenac in fish and effects on the molecular level; effects were discernible when plasma levels in the fish approached human therapeutic concentration (H T PC). Valenti et al (2012) observed significant decreases in binding at the therapeutic target and shelter-seeking behavior when fish plasma levels of sertraline exceeded H T PC, which was defined as either 142 ng mL À1 or 190 ng mL À1 .…”
Section: Relationships Between Responses and Plasma Concentrationsmentioning
confidence: 99%
“…Several studies have reported effects on fish at these concentrations of diclofenac, ranging from cytological and histological effects [14][15][16][17] to effects on gene expression [15,18]. Reported bioconcentration factors (BCFs) for diclofenac in rainbow trout varies between studies [10,11,16,18,19].…”
mentioning
confidence: 97%
“…Reported bioconcentration factors (BCFs) for diclofenac in rainbow trout varies between studies [10,11,16,18,19]. However, the most recent studies are in relatively close agreement, showing a stable BCF from water to blood plasma of approximately 4 [18,19]. We have recently shown effects on the global hepatic gene expression at exposure concentrations of diclofenac down to 1.6 g/L, even though the corresponding plasma concentration of exposed fish was relatively low (approximately 6 ng/mL) in comparison with the human therapeutic plasma concentrations (HTPC) of >420 ng/mL [20,21].…”
mentioning
confidence: 99%
“…Recent evidence suggests that diclofenac has the potential to cause adverse effects in various fish organs at an environmentally relevant concentration (Triebskorn et al, 2004). Diclofenac also affected gene expression in rainbow trout at 1 µg/L (Cuklev et al, 2011), and it activated VTG and CYP1A expression at 1 µg/L (Hong et al, 2007) and changed feeding behavior at 1000 µg/L (Nassef et al, 2010) in Japanese medaka. Contrary to these investigations, no observed effects were seen at concentrations of 320 µg/L in rainbow trout after 95 days' exposure (Memmert et al, 2013).…”
Section: Page 10 Of 48mentioning
confidence: 95%